2018
DOI: 10.1515/geochr-2015-0085
|View full text |Cite
|
Sign up to set email alerts
|

A review of radiometric analysis on soil erosion and deposition studies in Africa

Abstract: Soil erosion is one of the main soil degradation phenomena that threaten sustainable use of soil productivity thus affecting food security. In addition, it leads to reservoir storage capacity loss because of sedimentation. This not only affects water quantity but also water quality. Worldwide, annual loss in reservoir storage capacity due to sedimentation is 0.5 to 1%. Similarly, about 27% of land in Africa is largely degraded by erosion. As a result, there is need to minimize soil erosion and deposition throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The 137 Cs activities were found to be at a range of 1.44-8.77 Bq/kg and 1.01-10.99 Bq/kg for CR and M1 cores, respectively. This was in agreement with reports by Maina et al (2018) and Matisoff (2014) that there is low 137 Cs activities in the southern hemisphere. Comparing the 137 Cs activities of Lake Naivasha sediment with those recorded by Jeff and Shepherd (2009) for soils in Saiwa River watershed, Western Kenya, it was noted that the concentration of 137 Cs activities measured for the soils were also low, and they ranged from 0.00 to 4.28 Bq/kg in both depositional and disturbed sites.…”
Section: Distribution Of Artificial and Natural Radionuclides In Sedisupporting
confidence: 94%
See 1 more Smart Citation
“…The 137 Cs activities were found to be at a range of 1.44-8.77 Bq/kg and 1.01-10.99 Bq/kg for CR and M1 cores, respectively. This was in agreement with reports by Maina et al (2018) and Matisoff (2014) that there is low 137 Cs activities in the southern hemisphere. Comparing the 137 Cs activities of Lake Naivasha sediment with those recorded by Jeff and Shepherd (2009) for soils in Saiwa River watershed, Western Kenya, it was noted that the concentration of 137 Cs activities measured for the soils were also low, and they ranged from 0.00 to 4.28 Bq/kg in both depositional and disturbed sites.…”
Section: Distribution Of Artificial and Natural Radionuclides In Sedisupporting
confidence: 94%
“…This can be achieved by dating of sediment core using the natural or artificial Fallout Radionuclides (FRNs). The most common FRNs used in assessing recent sedimentation of reservoirs through dating of the sediment core include Cesium-137 ( 137 Cs), , and Beryllium-7 ( 7 Be) nuclides (Maina, Sang, Mutua, & Raude, 2018;Yang Hong Wu et al, 2010). The use of 210 Pb radionuclide in sediment dating along the core aids in characterizing changes of sediment input for a period of 100-150 years back (Dai et al, 2007;Yang & Turner, 2013;Yusoff, Zulkifli, Ismail, Abd, & Mohamed, 2015;Zalewska, Woroń, Danowska, & Suplińska, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previous studies (Yuan et al, 2011(Yuan et al, , 2014, strong correlations were found between Cu, Zn, and Pb concentrations, while there was a significantly negative correlation between Mn and Cu, Zn and Pb (Figure 2). This might cause by Mn oxides in sediments mainly origin from natural geochemical processes (Yuan et al, 2014;Maina et al, 2019). Besides, Mn/Fe oxides have a strong capacity to adsorb metals due to the large specific surface areas and regular porous structures (Xu L. et al, 2012;10.3389/fevo.2022.956903 TABLE 3 The Cdgt of labile metals (µg/L) in Chagan Lake and other areas.…”
Section: Spatial Profiles Of Labile Metals During the Ice-covered Periodmentioning
confidence: 99%
“…The re sults of gamma spec trom e try anal y sis are pre sented graph i cally for 12 soil pro files in the frame of the ver ti cal dis tri bu tions of radiocaesium con centra tions through the soil lay ers, fig. 4(1)-4 (12). In order to con vert in ven tory val ues [Bqm -2 ] to an nual erosive rates [tha -1 ], it was nec es sary to de ter mine a ref er ence point for the re search area.…”
Section: Re Sults Of Gamma-spec Trom E Try Anal Y Sis and Quan Ti Fi ...mentioning
confidence: 99%
“…The nu clear mod els with the de ter mi na tion of arti fi cial or i gin radionuclide 137 Cs in soil, were used to quan tify the rates of ero sion pro cesses. Through pre cipi ta tion, this radionuclide was strongly bind to the fine soil par ti cles in the top layer and can thus be con sid ered as be ing es sen tially non-ex change able [10][11][12]. The con cen tra tion of cae sium in top soil de creases in deeper lay ers un der the in flu ence of dif fu sion, me chan i cal or chem i cal re moval [13].…”
mentioning
confidence: 99%